Utilization of the Internet on Academic Information Systems IAIN Kendari - Amin, Ambar Sri Lestari (Advances in Social Sciences Research Journal, 2017)
This study discusses the internet which can be used to convey information quickly and widely through an online service that aims to determine the level of user assessments of the use of the Internet in support of academic activities and to obtain information difficulties or obstacles the use of internet in proses learning and teaching as well as the achievements of the increase in the number of students in education after using the internet at IAIN Kendari. The benefits of this research in order to sustain the intensity of management education in IAIN Kendari better, facilitate and expedite the learning activities in an effort to increase the productivity of education, and boosted achievement the number of students each year and can be used as one input to participate in providing facilities supporting the use of internet online services to support the academic activities in proses education. This type of research is mixed or mixed method research, data collection techniques used are questionnaires, interviews, observation and observation. This research is a field research (field research), the main source used is Kendari IAIN students who are still active in college and often use the internet, as well as other documents that support this research. The number of respondents of this study was 100 respondents to be sampled and analyzed using descriptive analysis. Interpretation of the data was based on the percentage of respondents. so the implementation of proses learning to use the internet in Kendari IAIN is needed. The review found that the use of the Internet is in the category very well and good for some applications services that are already online between 64%to 88%, providing an assessment quite 11% to 28%, and provide an assessment less category as much as 2% to 18%. Constraints in the implementation of the development of learning to use the internet in the classroom IAIN Kendari is the Internet network access and the signal is very weak so that the implementation is not optimal for the development of learning. Internet use in IAIN Kendari implications for the achievement in publishing information that shows the plan can be achieved can be evidenced by the number of college students who choose IAIN Kendari every year increasing numbers who obtained the information from the website IAIN Kendari.